Identification of three small nucleolar RNAs (snoRNAs) as potential prognostic markers in diffuse large B‐cell lymphoma - Mei‐wei Li; Feng‐xiang Huang; Zu‐cheng Xie; Hao‐yuan Hong; Qing‐yuan Xu; Zhi‐gang Peng (Cancer Medicine, 2023)
Abstract Background Diffuse large B‐cell lymphoma (DLBCL) is a non‐Hodgkin lymphoma with high mortality rates. Small nucleolar RNAs (snoRNAs) are tumor‐specific biological markers, but there are few studies on the role of snoRNAs in DLBCL. Materials and Methods Survival‐related snoRNAs were selected to construct a specific snoRNA‐based signature via computational analyses (Cox regression and independent prognostic analyses) to predict the prognosis of DLBCL patients. To assist in clinical applications, a nomogram was built by combining the risk model and other independent prognostic factors. Pathway analysis, gene ontology analysis, transcription factor enrichment, protein–protein interactions, and single nucleotide variant analysis were used to explore the potential biological mechanisms of co‐expressed genes. Results Twelve prognosis‐correlated snoRNAs were selected from the DLBCL patient cohort of microarray profiles, and a three‐snoRNA signature consisting of SNORD1A, SNORA60, and SNORA66 was constructed. DLBCL patients could be divided into high‐risk and low‐risk cohorts using the risk model, and the high‐risk group and activated B cell‐like (ABC) type DLBCL were linked with disappointing survival. In addition, SNORD1A co‐expressed genes were inseparably linked to the biological functions of the ribosome and mitochondria. Potential transcriptional regulatory networks have also been identified. MYC and RPL10A were the most mutated SNORD1A co‐expressed genes in DLBCL. Conclusion Put together, our findings explored the potential biological effects of snoRNAs in DLBCL, and provided a new predictor for DLBCL prediction.